Propionate-oriented kitchen waste fermentation for polyhydroxyalkanoate production by mixed microbial cultures - Xiaolei Zhang; Yingxue Sun; Shaoping Luo; Song Liu; R.D. Tyagi; Hongjie Wang; Ji Li (Bioresource Technology, 2026)

Comprehensive prevention and control technologies for karst tunnel construction safety: integration of advanced forecasting, monitoring, and emergency response - Yaodong Luo; Bing Luo; MingJun Li; Tiansi Zhang; Shaoping Yang; Luyao Ma; Bihe Zhang; Haoyan Zhang; Saeed Rehman (Carbonates and Evaporites, 2026)

Peptide-integrated bovine serum albumin hydrogel as a synergistic antifouling strategy for electrochemical detection of cardiac troponin I in serum - Qiushu Du; Peipei Wang; Zhen Song; Xiliang Luo; Shaoping Lv (Analytica Chimica Acta, 2026)

In situ sludge reduction assisted by alternating electrode-based electrochemical treatment - Xiaolei Zhang; Quanze Liu; Shaoping Luo; Yingxue Sun; Yong Li; Wenyi Dong; Patrick Drogui; Ji Li (Bioresource Technology, 2026)

A Statistical Quality-Control Framework for Sentinel-1 SAR Wind Speed Retrieval Based on First- and Second-Order Moments - Yan Wang; Xupu Geng; Yan Li; Xiaohui Li; Chenghan Luo; Shaoping Shang; Feng Zhang (Journal of Marine Science and Engineering, 2026)
Synthetic Aperture Radar (SAR) enables high-resolution sea-surface wind speed retrieval. However, the enhanced spatial resolution of SAR imagery introduces substantial challenges, from small-scale contamination sources that significantly degrade retrieval accuracy. Particularly in coastal regions, non-wind-related backscatter signals, such as ships and oil slicks, can severely bias wind speed estimates at sub-kilometer scales. In this study, the first-order moment (average, m1) and second-order moment (variance, m2) are computed from the normalized radar cross-section (NRCS) within sub-images of Sentinel-1 SAR data acquired in Interferometric Wide (IW) mode. Analysis reveals that clean-sea-surface signals in both VV and VH polarizations cluster around an approximately linear empirical trend, m2 = 2m1 + b, in the m1-m2 statistical feature space, whereas the examined contamination types deviate from this trend and occupy separable regions. Based on this characteristic, a quality-control framework is proposed for the systematic separation of clean sea surface from image noise (border noise and inter-swath stripe noise) and non-ocean targets (land contamination, bright targets, and dark spots). Validation using independent SAR data from the Taiwan Strait was conducted separately for native 10 m and height-adjusted 3 m buoy observations. For the native 10 m observations, the RMSE and MBE were essentially unchanged at 1.5 m/s and −0.3 m/s, respectively. For the height-adjusted nearshore observations, the RMSE decreased from 3.2 m/s to 2.1 m/s and the MBE changed from −1.5 m/s to −1.1 m/s.

Direct carbon recovery from raw wastewater for bioenergy production by anaerobic digestion - Yingxue Sun; Ji Li; Shaoping Luo; Yinghui Liu; R.D. Tyagi; Xiaolei Zhang (Bioresource Technology, 2026)

Spontaneous development and characterization of an endothelial-like cell line from mandarin fish Siniperca chuatsi - Jiaming Chen; Zhong Mi; Wenfeng Zhang; Panpan Luo; Shaoping Weng; Jianguo He; Chuanfu Dong (Fish & Shellfish Immunology, 2025)

Design, synthesis, and molecular docking study of isopimaroyl 1,2,4-triazole-thioether derivatives as anti-tumor agents - Juanjuan Liu; Ya Gao; Hu Chen; Guoyong Luo; Shaoping Yang (Natural Product Research, 2025)

A novel Toll receptor from Pacific white shrimp Penaeus vannamei is involved in immune defense against Vibrio parahaemolyticus infection - Shengwen Niu; Yuening Zhu; Ran Geng; Nuo Chen; Mengting Luo; Hongliang Zuo; Linwei Yang; Shaoping Weng; Jianguo He; Xiaopeng Xu (Aquaculture, 2023)

A novel chitinase Chi6 with immunosuppressive activity promotes white spot syndrome virus (WSSV) infection in Penaeus vannamei - Shengwen Niu; Yuening Zhu; Ran Geng; Mengting Luo; Hongliang Zuo; Linwei Yang; Shaoping Weng; Jianguo He; Xiaopeng Xu (Fish & Shellfish Immunology, 2023)

Alpha-aminoisobutyric acid incorporated peptides for the construction of electrochemical biosensors with high stability and low fouling in serum - Xiqin Yang; Min Chen; Zhanhua Zhang; Yang Li; Peipei Wang; Xiliang Luo; Shaoping Lv (Analytica Chimica Acta, 2023)

Effects of surgically implanted dummy ultrasonic transmitters on growth, survival and transmitter retention of bighead carp Hypophthalmichthys nobilis - Hongwei Luo; Xinbin Duan; Sheng Wang; Shaoping Liu; Daqing Chen (Environmental Biology of Fishes, 2015)

Effects of surgically implanted dummy ultrasonic transmitters on physiological response of bighead carp Hypophthalmichthys nobilis - Hongwei Luo; Xinbin Duan; Shaoping Liu; Daqing Chen (Fish Physiology and Biochemistry, 2014)